2022
DOI: 10.3390/antiox11030590
|View full text |Cite
|
Sign up to set email alerts
|

A PON for All Seasons: Comparing Paraoxonase Enzyme Substrates, Activity and Action including the Role of PON3 in Health and Disease

Abstract: Paraoxonases (PONs) are a family of hydrolytic enzymes consisting of three members, PON1, PON2, and PON3, located on human chromosome 7. Identifying the physiological substrates of these enzymes is necessary for the elucidation of their biological roles and to establish their applications in the biomedical field. PON substrates are classified as organophosphates, aryl esters, and lactones based on their structure. While the established native physiological activity of PONs is its lactonase activity, the enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 115 publications
2
19
0
Order By: Relevance
“…PON1 and very low levels of PON3 are found in serum bound to HDL by the hydrophobic N-terminal leader sequence [ 20 ]. All PON enzymes have an antioxidant capacity and are known to decrease the risk of atherosclerosis development [ 21 , 22 ]. Despite having that effect, the physiological substrates of PONs remain unknown [ 23 ].…”
Section: Properties Of Paraoxonasementioning
confidence: 99%
“…PON1 and very low levels of PON3 are found in serum bound to HDL by the hydrophobic N-terminal leader sequence [ 20 ]. All PON enzymes have an antioxidant capacity and are known to decrease the risk of atherosclerosis development [ 21 , 22 ]. Despite having that effect, the physiological substrates of PONs remain unknown [ 23 ].…”
Section: Properties Of Paraoxonasementioning
confidence: 99%
“…PON-1 is a calcium-dependent hydrolytic enzyme that is produced in the liver and bound to high-density lipoprotein (HDL) cholesterol [ 9 ]. Many studies have shown the important role of PON-1 in cardiovascular disease (CVD) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, evidence proposes a possible role for PON-1 in potentiating CVD associated with chronic kidney disease. Many studies have demonstrated an association between low-circulating PON-1 activity and adverse CVD outcomes in CKD settings [ 7 , 8 , 9 , 10 ]. In fact, lower PON-1 levels were associated with higher CRP, lower HDL3, and adverse future CVD outcomes [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…PON3 is synthesized in the liver and released into the blood where it circulates bound to high-density lipoproteins. PON3 gene expression is primarily observed in the liver and kidney, and it is also distributed to various other tissues, including the lung, pancreas, intestine, and eyes [ 15 , 16 ]. While there is some overlap in substrate specificity, PON3 is established primarily as a lactonase.…”
Section: Introductionmentioning
confidence: 99%
“…While there is some overlap in substrate specificity, PON3 is established primarily as a lactonase. Although some recent studies have established arachidonic acid and its derivatives as the physiological substrates for PON3 [ 15 , 17 , 18 ], the physiological relevance of their metabolism by PONs remains enigmatic. It has been demonstrated that PON3 hydrolyzes six-membered δ-lactones, which are similar to CTS compounds in their structure [ 15 , 17 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%